Cytochemical evaluation of gamma-glutamyl-transpeptidase activity in cervical smears - De Camargo, J. L.V.; De Oliveira, M. L.C.S.; Mantovani, M. S.; Gaiotto, M. E.; De Mattos, M. C.F.I.; Traiman, P. (My University, 1988)
The cervicovaginal smears of 43 patients attending an outpatient service for early cancer detection were cytochemically studied for the presence of gamma-glutamyl-transpeptidase (GGT) in epithelial cells. This was done in order to evaluate such an enzyme phenotype as a marker for cancer development. The results showed that 70% of the 38 patients with a cytologic diagnosis of 'inflammatory' or preneoplastic/neoplastic conditions had GGT-positive cells in their smears. None of the five cytologically normal cases showed any epithelial cell with GGT activity. Although most of the GGT-positive cells were metaplastic, some morphologically normal, dysplastic or neoplastic cells also expressed the enzyme. The data suggest that cytochemically detectable transpeptidase activity appears whenever alterations of the normal epithelial microenvironment occurs, but is not necessarily linked on the carcinogenic process. Therefore, cytochemically GGT-positive cells should not be used as an indicator of neoplastic transformation of the cervical epithelium.